2021
DOI: 10.3390/biomedicines9060635
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Perspective of Nanoparticle Mediated Therapeutic Targeting in Breast Cancer: An Odyssey of Endoplasmic Reticulum Unfolded Protein Response (UPRER) and Beyond

Abstract: Breast cancer (BC) is the second most frequent cause of death among women. Representing a complex and heterogeneous type of cancer, its occurrence is attributed by both genetic (gene mutations, e.g., BRCA1, BRCA2) and non-genetic (race, ethnicity, etc.) risk factors. The effectiveness of available treatment regimens (small molecules, cytotoxic agents, and inhibitors) decreased due to their poor penetration across biological barriers, limited targeting, and rapid body clearance along with their effect on normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 202 publications
1
3
0
Order By: Relevance
“…This is accomplished by reducing the activation of selfreactive T cells and delaying the beginning of illness. This disorder manifests itself in a patient whenever their immune system begins to attack their own body (22). These findings provide credence to the findings by (23), who found that the blood IL-38 concentrations of individuals with Graves' disease and Hashimoto's illness were significantly different from those of healthy controls.…”
Section: Discussionsupporting
confidence: 83%
“…This is accomplished by reducing the activation of selfreactive T cells and delaying the beginning of illness. This disorder manifests itself in a patient whenever their immune system begins to attack their own body (22). These findings provide credence to the findings by (23), who found that the blood IL-38 concentrations of individuals with Graves' disease and Hashimoto's illness were significantly different from those of healthy controls.…”
Section: Discussionsupporting
confidence: 83%
“…The importance of UPR for drug resistance has planted the idea of inducing an overload of ER stress (166). This could be achieved by certain nanoparticles or by the proteasome inhibitor bortezomib, the latter being already used to treat certain haematopoietic cancers.…”
Section: X-box Binding Protein-1mentioning
confidence: 99%
“…Several authors have already reported that the non-covalent conjugation of anticancer molecules with graphene oxide sheets may be the path to more targeted delivery at the cellular level and a possible escape from tumor resistance [ 7 , 8 ]. Structural modification aimed at solving these limitations and reducing the cytotoxicity of the material is an interesting strategy for the biological applications of graphene [ 9 ]. Among the possible structural modifications in graphene particles, the association with dendrimers, such as polyamide amine (PAMAM), can provide better cell uptake since PAMAM dendrimers have been reported to be able to associate electrostatically with lipid membranes to form amphiphilic bilayers and thus promote cell uptake [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%